أهمية تعليم اللغة العربية لطلاب الفصل الثامن في المدرسة المتوسطة الخيرية الأهلية سنفالي دلي سردنج اندونيسيا - Silvia Ardani; Fahrurrozi. S (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The urgency of a language can be seen from its function which has an important role in the life of the elderly, language has at least three functions, namely ideational, interpersonal social, and textual. So that from this function language cannot be separated from human life. Language and people are like two inseparable sides of a coin that transcend each other. So that language itself greatly determines the survival of human beings in learning, this study aims to explore the urgency of learning Arabic among grade VIII students at Madrasah Tsanawiyah PAB Sampali. Using a qualitative approach and a descriptive method, this study analyzes the importance of deepening the understanding of Arabic in the context of formal education. Data was collected through interviews and observations of students and analysis of supporting documents. The findings of the study highlight that learning Arabic not only supports students' communication skills in the language, but also strengthens their religious identity. The implications of this study provide a solid basis for the development of a more effective and relevant curriculum in the teaching of Arabic in madrasas.